The Effects of Peanuts and Tree Nuts on Lipid Profile in Type 2 Diabetic Patients: A Systematic Review and Meta-Analysis of Randomized, Controlled-Feeding Clinical Studies - Jia-yue Xia (Frontiers Media S.A., 2021)
Background: Type 2 diabetes mellitus was found to be associated with metabolic disorders, particularly abnormal glucose and lipid metabolism. Dietary food choices may have profound effects on blood lipids. The primary objective of this study was to examine the effects of peanuts and tree nuts intake on lipid profile in patients with type 2 diabetes.Methods: According to preferred reporting items for systematic reviews and meta-analysis guidelines, we performed a systematic search of randomized controlled clinical trials and systematic reviews published in PubMed, Web of Science, Embase, Scopus, and Cochrane library, from inception through June 2021. Studies in populations with type 2 diabetes, which compare nuts or peanuts to a controlled-diet group were included. We used the mean difference with 95% CIs to present estimates for continuous outcomes from individual studies. In addition, we used the GRADEpro tool to evaluate the overall quality of evidence.Results: Sixteen studies involving 1,041 participants were eligible for this review. The results showed that peanuts and tree nuts supplementation did not induce significant changes in low-density lipoprotein-cholesterol (LDL-C) (mean difference = −0.11; 95%CI: −0.25 – 0.03, p = 0.117) and high-density lipoprotein-cholesterol (HDL-C) (mean difference = 0.01; 95%CI: −0.01 – 0.04, p = 0.400) in patients with type 2 diabetics. In addition, we found that peanuts and tree nuts intake may cause a significantly reduction in total cholesterol (TC) (mean difference = −0.14; 95%CI: −0.26 – −0.02, p = 0.024) and triglyceride (TG) (mean difference = −0.10; 95%CI: −0.17 – −0.02, p = 0.010). In the subgroup analysis, a significantly greater reduction in TC was observed in studies which duration was <12 weeks (mean difference = −0.22; 95%CI: −0.37 – −0.08, p = 0.002). The quality of the body of evidence was “moderate” for TC and TG, the quality of evidence for LDL-C and HDL-C were “low.”Conclusion: Our findings suggest that consuming peanuts and tree nuts might be beneficial to lower TC concentration and TG concentration in type 2 diabetics subjects. Furthermore, peanuts and tree nuts supplementation could be considered as a part of a healthy lifestyle in the management of blood lipids in patients with type 2 diabetes. Given some limits observed in the current studies, more well-designed trials are still needed.